RETRACTED: International north-south transport corridor: New economic and trade opportunities for India and Armenia - Grigoryan Karen; Khachikyan Sos; Avetisyan Artur; Egnatosyan Siranush (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001